Catalytically Active Gold Nanomaterials Stabilized by N‐heterocyclic Carbenes. Issue 20 (20th September 2021) - Eisen, Constantin; Chin, Jia Min; Reithofer, Michael R.
Abstract: Solid supported or ligand capped gold nanomaterials (AuNMs) emerged as versatile and recyclable heterogeneous catalysts for a broad variety of conversions in the ongoing catalytic ′gold rush′. Existing at the border of homogeneous and heterogeneous catalysis, AuNMs offer the potential to merge high catalytic activity with significant substrate selectivity. Owing to their strong binding towards the surface atoms of AuMNs, NHCs offer tunable activation of surface atoms while maintaining selectivity and stability of the NM even under challenging conditions. This work summarizes well‐defined catalytically active NHC capped AuNMs including spherical nanoparticles and atom‐precise nanoclusters as well as the important NHC design choices towards activity and (stereo‐)selectivity enhancements. Abstract : NHC stabilized gold nanomaterials are emerging as a promising material for catalysis, and this report aims to introduce them and review the current state of art.